(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background. Early childhood caries (ECC) remains one of the most prevalent chronic diseases in children worldwide. Feeding practices during infancy play a crucial role in shaping oral homeostasis and caries susceptibility. Objective. To evaluate the impact of different feeding practices on dental status and caries development in children of early age. Materials and Methods. A total of 173 children aged 6 months to 6 years with ECC were examined. Participants were stratified by age and feeding practice (breastfeeding, mixed feeding, artificial feeding). Dental status was assessed using caries intensity (dmft index), caries prevalence, caries increment, and oral hygiene indices. Statistical analysis was performed using SPSS software with significance set at p<0.05. Results. Artificial feeding was associated with significantly higher caries intensity and prevalence compared to breastfeeding and mixed feeding. Caries indicators increased with age in all groups; however, the most pronounced progression was observed in artificially fed children. Conclusion. Feeding practices are a significant determinant of ECC development. Artificial feeding increases caries risk and should be considered when developing individualized preventive strategies.